Challenges of practicing ethical leadership in Sudanese universities - Taha Mitugn, Ahmed (Technium Social Sciences Journal, 2021)
This study aimed to examine the challenges of practicing ethical leadership in Sudanese universities. To this end, the study used a contemporary mixed research design. Simple random sampling techniques took three hundred sixty-five (365) participants. Quantitative data were collected from teachers using a closed questionnaire. At the same time, interviews were conducted with university directors, deans of faculties, and heads of departments. Quantitative data were analyzed using descriptive and inferential statistics such as mean scores, one-sample t-test, and linear regression analysis. Qualitative data were objectively analyzed and interpreted. The study found that addressing the extent of practicing ethical leadership in Sudanese universities was average and needed further investigations. The study results clearly show that the challenges of practicing ethics showed a high average in terms of internal factors by communicating moral values when dealing with subordinates. Also, honesty and integrity are considered. It is also clear that the mean scores of external factors and ethical leadership behavior and actions were high, indicating that faith and values are statistically unimportant factors for ethical leadership practice in Sudanese universities. The study recommended the necessity of paying attention to the practice of ethical leadership in Sudanese universities in all its dimensions, facing challenges with scientific foundations, and encouraging employees, including university administrators, deans of colleges, and heads of departments, to practice ethical behaviors and values because of their importance in universities.